2021
DOI: 10.1149/1945-7111/ac3b05
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Fe-MOF Exhibits Higher Oxygen Evolution Ability by Electronic Modulation of Sodium Hypochlorite

Abstract: Development of robust alkaline oxygen evolution reaction electrocatalysts is crucial for the efficiency of water splitting. Herein, Fe-MOF nanocones array on nickel foam are synthesized by introducing sodium hypochlorite, leading to Cl substitution of terephthalic acid in Fe-MOFs (Fe-MOF-Cl/NF). Experimental results show that Fe-MOF-Cl/NF exhibits enhanced OER activity over Fe-MOF/NF, lowering η 50 from 292.4 to 222.7 mV. In combination with density function theory calculations, the improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…S2 and S3,† ZIF-67(Co) and MIL-53(Fe) presented rhomboidal dodecahedron nanocrystal and nanosheet structures, respectively, which are consistent with studies reported in the literature. 34,35 The hierarchical structure of MIL-53(Fe)@ZIF-67(Co) is shown in Fig. 1c.…”
Section: Resultsmentioning
confidence: 99%
“…S2 and S3,† ZIF-67(Co) and MIL-53(Fe) presented rhomboidal dodecahedron nanocrystal and nanosheet structures, respectively, which are consistent with studies reported in the literature. 34,35 The hierarchical structure of MIL-53(Fe)@ZIF-67(Co) is shown in Fig. 1c.…”
Section: Resultsmentioning
confidence: 99%
“…The metal center of a MOF is a multi-valent metal ion, which acts as the coordination active point in the reaction, and these coordination sites can be changed, so that the material can easily form a regular and adjustable three-dimensional structure. Considering the difficulty of the material source and the properties of the metal itself, Ni 2+ , 23,24 Fe 3+ , 25 Cu 2+ , 26 Co 2+ 27 and other transition metals are commonly used to synthesize MOF materials. 28…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] The metal center of a MOF is a multi-valent metal ion, which acts as the coordination active point in the reaction, and these coordination sites can be changed, so that the material can easily form a regular and adjustable three-dimensional structure. Considering the difficulty of the material source and the properties of the metal itself, Ni 2+ , 23,24 Fe 3+ , 25 Cu 2+ , 26 Co 2+27 and other transition metals are commonly used to synthesize MOF materials. 28 Nickel is widely used as an OER electrocatalyst because of its good oxophilicity and the best oxygen evolution ability among the transition metals 29,30 and so Ni-MOFs have been attracting increasing attention in the field of catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that Fe and Ni are magnetic ions, and their complex has excellent OER catalytic activity. [16][17][18][19][20] Unfortunately, from a broader perspective, the role of magnetism in the compounds of Fe and Ni in increasing their OER activity is still underestimated.…”
mentioning
confidence: 99%